Uji Kelincahan Terhadap Pelatihan Ladder Drill Quick Feet Dan Ladder Drill The Boxer Pada Atelt Ikasi Sidoarjo - Puriana, Ramadhany Hananto; Suryansah, Suryansah - (Jurnal Porkes, 2019)
Physical condition is a very important component in conducting sports activities both in the form of achievement or learning. Agility is a dominant component in sports activities Fencing is used to attack and avoid the opponent's attacks. Fencing is one of the dominant sports using biomotor components of foot agility. The purpose of this study was to determine the effect of quick feet and the boxer drill ladder training on increasing leg agility to support one of the techniques aimed at attacking and avoiding opponent's attacks. This research is a "quantitative" research method with quasi-experimental techniques, research conducted strictly to find out the cause and effect between variables. Data analysis techniques in this study were to test multiple normality tests, homogeneity tests, and hypothesis testing.